Meningkatkan Hasil Belajar Bola Voli Melalui Modifikasi Alat - Ainun, Ainun; Kahar, Irsan; Jalil, Rasyidah (Universitas Hamzanwadi, 2025)
The purpose of this study was to determine whether tool modification can improve volleyball learning outcomes. This research method uses quantitative descriptive. The sample size of this study was 24 students. The population in this study were all 8th grade students of SMPN 3 Bajo. The results of volleyball learning research 25% and the remaining 65% still have not reached the minimum completeness limit set. Student learning outcomes in volleyball learning improved when compared to data in the pre-cycle. The effective aspect found an average percentage of students of 33.3% which was stated with insufficient criteria, in cycle II, the average percentage of students was 87.5% which was also stated as good. The Cognitive aspect found an average student percentage of 41.7 which was stated with insufficient criteria in cycle I. After learning in cycle II 91.7% which is also stated with very good criteria. In the psychomotor aspect, cycle I found that the target achievement plan, which was originally 65%, was achieved. Of the 24 students, the number of passes in the pre-cycle was 25%, cycle I 71%, cycle II 92%. Based on the percentage data, it shows that there is an increase in student learning outcomes in each cycle. The increase in percentage from pre-cycle to cycle I 46% while from cycle I to cycle II 21% is evidence that the actions taken through game modifications to the problems that occur in volleyball learning are successful.